The Effect of Green Tea Extract Supplementation on Superoxide Dismutase Levels and Endometriosis Lesions: A Clinical Trial in Mice - Trisetiyono, Yuli; Artanto, Yosef Adi (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2024)
Endometriosis is a gynaecological disorder characterised by the presence of endometrial tissue outside the uterine cavity. It affects approximately 10-15% of females of reproductive age. Oxidative stress has been identified as a significant contributing factor to the development and progression of endometriosis. In this study, we investigated the effect of green tea extract on the endometriotic implant area and serum superoxide dismutase (SOD) levels in a rat model of endometriosis. Twenty-six female Balb/c rats were randomly divided into the experimental group (EG) and the control group (CG). All subjects in the EG received green tea extract (3 mg daily) for 14 days. On the fourteenth day, endometriosis was induced in all subjects (both EG and CG). The endometriotic implant area and serum SOD levels were assessed 14 days after induction. The endometriotic implant area in the green tea extract-treated group was significantly lower than that in the control group (p=0.022, RR=0.455, 95% CI=0.065-0.96). Serum SOD levels in the EG and CG were 5.33Â±0.52 ng/ml and 5.20Â±0.91 ng/ml, respectively (p=0.507). Green tea extract effectively inhibited the progression of endometriotic implants and increased serum SOD levels in the endometriosis-induced rat model. These findings suggest that the anti-angiogenic and antioxidant properties of green tea may have therapeutic potential in managing endometriosis.